Teaching Vectors to Junior Secondary School Learners: A Comparison of Two Approaches - Chirume, Silvanos (Innovare Journal of Education, 2023)
The purpose of this study was to investigate whether Form 2 learners taught using the position and movement approach (Experimental group) performed better in a test on Vectors than their counterparts taught using the non-geometric or matrix approach (Control group). A comparison of the two approaches in relation to the Gestalt and the Behaviourist learning theories was also discussed. The mixed research approach (QUANT- Qual) was used. For the QUANT part, the quasi-experimental approach involving the pre-test – post-test control group design with 50 randomly chosen learners (25 in each group) was used. Results showed that, generally, the Experimental group performed better than the Control group, although the findings could be taken with caution due to the small sample sizes and the lack of a true experiment. For the Qual approach, four learners were purposively sampled. The learners were asked to talk about their experiences and performances during learning. An attempt to relate these experiences with the Gestalt and Behaviourist learning theories was also made. It could be concluded that the position and movement approach fitted quite well with the Gestalt Theory, whereas the matrix approach fitted with Behaviourism. These results and findings could help to inform the theory and practice of teaching Vectors in particular and other Math topics in general. There is also a need for further research to see if consistencies in these views could be established.